POTRET WAJAH PENDIDIKAN KEWIRAUSAHAAN DI PERGURUAN TINGGI : SUDAH EFEKTIFKAH ? - LUDWINA PORMES (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
This research aims to find out how the process of education or entrepreneurial courses at the college level and its influence on student creativity in creating and developing the spirit of enterpreunership among students. This research is explorative and qualitative by looking at and concluding some of the curriculum and methods of entrepreneurship education that are common in Indonesia. This research is expected to be able to support universities in developing methods, curriculum and educators who are competent in the teaching process of entrepreneurial courses so as to produce creative young entrepreneurs from among universities